PENINGKATAN KOMPETENSI DALAM PENGEMBANGAN BAHAN AJAR BERORIENTASI TPACK BAGI GURU SD DI KOTA SERANG - Saefulloh, Febri; Jamaludin, Ujang; Tisnasari, Sundawati; Fajrudin, Lili; Sari, Novita (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2024)
Today's technological developments are growing rapidly and entering all aspects of life, including education. This development should be utilized by teachers to create interesting and innovative learning. Interesting learning is not only determined by the way the material is delivered, but also by the media and resources used in the learning. In this digital era, teachers must be sensitive to it. Millennial era students are very proficient and dependent on technology, for this reason ateaching material is needed that can facilitate students in learning which can be accessed easily anywhere and anytime. The current Pandemic era requires learning to be done online. Library books certainly cannot be accessed from home. For this reason, teaching materials based on TPACK (Technological Pedagogical Content Knowledge) are needed. Sultan Ageng Tirtayasa University as one of the LPTK has a moral responsibility in providing professional, competent, and creative educators. For this reason, it is necessary to carry out activities that can facilitate teachers to develop their abilities in designing and developing TPACK-based teaching materials. This activity aims to assist and develop teachers' abilities in developing creative and innovative teaching materials based on TPACK. In achieving this goal, the stages of the activity are designed, namely preparation of training modules and preparation of instructors, implementation including presentation of material from resource persons related to TPACK-oriented teaching materials, and conducting workshops and mentoring periodically. The last stage is evaluation which aims to measure the effectiveness of the program. The output of this activity is compiling TPACK-oriented teaching materials